Cane productivity and attributes, and yield gaps of different sugarcane (Saccharum officinarum) varieties in south-western Punjab, India - SANDHU, AMARJEET SINGH; SINGH, PRITPAL; KAUR, NAVNEET (The Indian Journal of Agricultural Sciences, 2025)
Sugarcane (Saccharum officinarum L.) varieties differ significantly for agronomic attributes which affect their yield potential in response to management practices. The present study was carried out during 2020–21 and 2021–22 at four different locations in Bhatinda (Sukha Singh Wala, Bhai Roopa, Dayalpura Mirza and Mehta villages), Punjab to investigate the variation in agronomic attributes of three early maturing (Co J-85, Co J-64, Co Pb-96) and two late maturing (Co Pb-98 and Co J-88) sugarcane varieties at four different locations. These results revealed that variety Co Pb-98 outperformed with significantly (P<0.05) higher cane height (23.8%), stalk diameter (17.9%), number of tillers/plant (34.4%), stalk height (22.8%), number of internodes (26.7%) and internode length (42.9%) over Co J-64, which contribute towards cane productivity. The cane productivity exhibited a linear significant relationship with single cane weight (R2=0.753; P<0.05). These results revealed existence of yield gaps of 2.9-8.9 Mg/ha over the state average yield; the highest for Co J-85 ( 207%) than the Co Pb-98 variety. Regardless of the sugarcane variety, a significantly higher single cane weight (17.1%) and cane productivity (11.1%) at Dayalpura Mirza as compared to at Sukha Singh Wala showed that high soil salinity was responsible for decreased cane productivity.